Synergic antibacterial activity of some essential oils from Lamiaceae - Sh. Fahimi; H. Hajimehdipoor; H. Shabanpoor; F. Bagheri; M. Shekarchi (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Despite the vast production of new antibiotics in the last three decades, resistance to these drugs by microorganisms has increased and essential oils (EOs) have been recognized to possess antimicrobial properties. Methods:  In the present study, EOs obtained from aerial parts of Thymus vulgaris L., Lavandula angustifolia Mill., Rosmarinus officinalis L. and Mentha piperita L., were evaluated for their single and binary combined antibacterial activities against four Gram-positive and Gram-negative pathogenic bacteria: Staphylococcus aureus, Bacillus cereus, Escherichia coli and Pseudomonas aeruginosa. Results: The results exhibited that some of the tested essential oils revealed antibacterial activities against the examined pathogens using broth microdilution method. Maximum activity of the testedessential oils was obtained from the combination of T. vulgaris and M. piperita essential oils against Staphylococcus aureus (MIC= 0.625 mg/mL). Conclusion: Combinations of the essential oils in this study showed synergic action against some pathogenic microorganisms which could be considered in medical and food industries as preservatives.